AN ANALYSIS OF TRAUMATIC HYPHEMA WITH SECONDARY GLAUCOMA IN A 6-YEAR-OLD CHILD: A CASE REPORT : TRAUMATIC HYPHEMA - Agatha Gracecia Nindra Clarissa; Kantika Prinandita; Shirly Gunawan (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Hyphema is a condition where blood collects in the anterior chamber of the eye, usually caused by blunt trauma that results in tearing of the uveal blood vessels (traumatic hyphema). This condition is an ophthalmological emergency that can lead to permanent vision loss if not treated promptly. Global data indicates the incidence of traumatic hyphema is 12 per 100,000 patients. In Indonesia, Cicendo Eye Hospital reports that 88.3% of ocular trauma in children is caused by blunt trauma. Methods: This case report describes a 6-year-old boy who complained of pain in his left eye for 2 days, accompanied by blurred vision, a sensation of darkness, glare when exposed to light, excessive tearing, and a foreign body sensation. Results: The patient had a history of ocular trauma due to a sports-related injury three days prior. Visual acuity examination showed 6/6 OD and 1/300 OS. Physical examination of the left eye revealed edema of the superior and inferior eyelids, conjunctival and scleral hyperemia with ciliary injection, and blood filling of the anterior chamber reaching approximately 60–70% of the chamber height. The iris and pupil were not assessable. Tonometry revealed elevated left ocular intraocular pressure. The patient was diagnosed with a grade III traumatic hyphema with secondary glaucoma. Conclusion: Education and conservative management were provided. After 6 days, symptoms improved, the hyphema regressed, and IOP decreased.